2021
DOI: 10.1038/s41420-021-00527-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-326 attenuates immune escape and prevents metastasis in lung adenocarcinoma by targeting PD-L1 and B7-H3

Abstract: Tumor-infiltrating T cells are highly expressive of inhibitory receptor/immune checkpoint molecules that bind to ligand expressed by tumor cells and antigen-presenting cells, and eventually lead to T cell dysfunction. It is a hot topic to restore T cell function by targeting immune checkpoint. In recent years, immunotherapy of blocking immune checkpoint and its receptor, such as PD-L1/PD-1 targeted therapy, has made effective progress, which brings hope for patients with advanced malignant tumor. However, only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Each of which has the capacity to regulate M2 macrophages and cancer characteristics [ 33 , 34 ]. Hsa-miR-326 is involved in the regulation of programmed death ligand 1 (PD-L1) and CD8+ T cells [ 35 ]. Transcription factors are important targets for non-coding RNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of which has the capacity to regulate M2 macrophages and cancer characteristics [ 33 , 34 ]. Hsa-miR-326 is involved in the regulation of programmed death ligand 1 (PD-L1) and CD8+ T cells [ 35 ]. Transcription factors are important targets for non-coding RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Shao et al . reported that hsa-miR-326 regulates the expression of immune checkpoint molecules, PD-L1 and B7-H3, which affect the cytokine profile of CD8+ T cells as well as lung adenocarcinoma cell migration [ 35 ]. PD-L1 and B7-H3 have been identified as targets for immunotherapeutic intervention in OS [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies implied that improving immune function and inhibiting immune escape can inhibit malignant progression of LUAD [34][35][36]. NK cells take a crucial part in the prognosis of tumors because they can induce immune responses after cancer treatment [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-148a overturned cell migration and invasion by Wnt1 in NSCLC [14]. Besides, miR-7-5p subdued tumor metastasis in NSCLC via binding NOVA2 [15]. What's more, Cheng et al demonstrated that miR-485-5p content was reduced in NSCLC [16].…”
Section: Introductionmentioning
confidence: 99%